Increase of Bcl-2/Bax ratio corelated with decrease of lymphocyte apoptosis: a study in the bronchiolus and lung of asthmatic mice - Hasan, Taufiq Hidayat; Yuliarto, Saptadi; Barlianto, Wisnu; Sujuti, Hidayat; Kusuma, HMS Chandra (Academic Journals, 2013)
The failure of lymphocyte apoptosis is one of the factors causing chronic airway inflammation in asthma. Some studies indicate the role of Bcl-2 in inhibition of lymphocyte apoptosis, but still little research is on the role of Bax and its relationship to Bcl-2 in asthma. The purpose of this study was to prove the role of Bcl-2-lymphocyte in inhibition of lymphocyte apoptosis and decrease in Bax-lymphocytes in bronchiolus and lung of asthmatic mice. This study was a randomized control group design. Subjects were Balb/c mice which divided into 2 groups: non-asthma and asthma. Asthma group were sensitized with ovalbumin intraperitoneally on day 0 and 14, followed by inhalation every 2 to 3 days for 6 weeks. At week 8, all subjects terminated. Bcl-2 and Bax-lymphocytes expression were examined with immunohistochemical method, whereas apoptotic lymphocytes by Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) method. Statistical analysis used was the independent sample t-test and regression analysis, with 95% confidence interval. Bronchial and lung specimens were obtained from 18 subjects (9 from each group). The ratio of apoptotic lymphocytes decreased in the asthma group (p = 0.003), Bcl-2-lymphocytes increased in the asthma group (p <0.001), and Bax-lymphocytes decreased in the asthma group (p = 0.003). There was a strong negative correlation (r = -0.66, r2 = 0.43, p = 0.003) between the Bcl-2 and lymphocyte apoptosis. There was also a strong negative correlation (r = -0.56, r2 = 0.35, p = 0.009) between the ratio Bcl-2/Bax and lymphocyte apoptosis. However, no significant relationship was found between Bax-lymphocytes and lymphocyte apoptosis (r = 0.36, r2 = 0.13, p = 0.15). Increasing the ratio of Bcl-2/Bax inhibit lymphocyte apoptosis where Bcl-2 plays more role than Bax.